2002
DOI: 10.1063/1.1436531
|View full text |Cite
|
Sign up to set email alerts
|

Low Stokes shift in thick and homogeneous InGaN epilayers

Abstract: The optical properties of thick InxGa1−xN layers have been studied using optical absorption and cathodoluminescence techniques. The indium composition x of the layers ranged from 0.03 to 0.17 as determined by Rutherford backscattering measurements. The difference between the band gap and the peak emission energy (Stokes shift) was found to be considerably smaller than reported in the past for these alloys. Monochromatic images show that light emission from most of the film is homogeneous and is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 16 publications
6
43
0
2
Order By: Relevance
“…The broadened X-ray diffraction peak seen in the insert in Dependences of the absorption edge and luminescence energy on the mole fraction of In in an InGaN alloy have been previously reported. 30,31 The indium content, which corresponds to the 420 nm PL peak position is ~10-15%, and this agrees very well with the indium fraction obtained from X-ray diffraction (~14%). The stronger peak at 480-520 nm corresponds to the indium content of ~15-20%, which is also possible in our sample.…”
Section: Resultssupporting
confidence: 75%
“…The broadened X-ray diffraction peak seen in the insert in Dependences of the absorption edge and luminescence energy on the mole fraction of In in an InGaN alloy have been previously reported. 30,31 The indium content, which corresponds to the 420 nm PL peak position is ~10-15%, and this agrees very well with the indium fraction obtained from X-ray diffraction (~14%). The stronger peak at 480-520 nm corresponds to the indium content of ~15-20%, which is also possible in our sample.…”
Section: Resultssupporting
confidence: 75%
“…8 Our XRD measurements clearly indicate strong indium aggregation processes in our sample and this observation is in agreement with previous reports. [4][5][6][7][8] The comments also argued the interpretation of our scanning electron microscopy ͑SEM͒ and energy dispersive x-ray spectrometry ͑EDS͒ results. Our InGaN films have been found to have mirrorlike surface by scanning electron microscopy ͑SEM͒ and transmission electron microscopy ͑TEM͒ measurements.…”
supporting
confidence: 82%
“…However, by selectively focusing the electron beam inside and outside the cluster, we have demonstrated that the double CL peak arises from phase segregation. Srinivasan et al 8 have also performed CL images and clearly shown that composition fluctuations do contribute to the CL spectra. It is not a consequence of partially relaxed InGaN films of uniform indium composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such CL signal, arising from regions with slightly larger In contents, is fully compatible with the broadening of the HRXRD reflections and may be attributed to dot-like In-rich regions near the surface of the InGaN epilayers. 31,32 In the rest of epilayers the CL signal was highly homogeneous, with no evidence of InN-rich segregated phases. B. Raman scattering by A 1 (LO) and E 2h phonons Figure 3 shows Raman spectra of four representative In x Ga 1Àx N epilayers.…”
Section: Sample In Content (X)mentioning
confidence: 95%